Program Kegiatan Perbaikan dan Perawatan Mesin dan Alat Rumah Tangga dalam Meningkatkan Kemandirian Ekonomi Masyarakat di Desa Sedati, Sidoarjo - M. Andrean Maulana (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This household appliance and machine repair and maintenance program is designed to promote economic independence for the community in Sedati Village, Sidoarjo, by strengthening technical skills based on local potential. The underlying problem of this activity is the community's high dependence on external repair services and limited ability to handle household appliance damage independently. Therefore, the Asset-Based Community Development (ABCD) approach is used, which focuses on utilizing the assets, potential, and capacity already possessed by the community. The program is implemented in a participatory manner, with stages including identification and mapping of local assets, joint planning, technical skills training, hands-on practice, and activity evaluation. The results show an increase in the community's ability and understanding in performing simple household appliance maintenance and repairs. Furthermore, the community is beginning to recognize economic opportunities from their skills, thus potentially developing independent repair service businesses. Thus, the application of the ABCD approach in this activity has proven effective in strengthening the community's economic independence in a sustainable manner through optimizing local assets. Going forward, ongoing mentoring efforts are needed to ensure that the potential that has been established can continue to develop and provide broader economic benefits.